Penerapan Media Ajar Digital “Misi Mencari Arti Nama” untuk Meningkatkan Hasil Belajar Muatan Bahasa Indonesia Materi Tanda Baca Kelas II SDN Krembangan Selatan VII18 (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to determine the impact of implementing the digital learning media with picture stories "Misi Mencari Arti Nama" on the learning outcomes of class II students at SDN Krembangan Selatan VII18 on Indonesian language content on punctuation material. This research uses PTK to review the success of the learning process. Each cycle has four stages, namely planning, implementation, observation and reflection. The subjects of this research were 20 students in class II at SD Negeri Krembangan Selatan VII18 and the method used was a quantitative method with qualitative descriptive analysis techniques. Based on research findings, class II students at SDN Krembangan Selatan VII18 in Surabaya can achieve better learning outcomes after applying learning media during the learning process.  This can be seen from the increase in the average value of pre-cycle, cycle 1, and cycle 2, which respectively amounted to 50.16 (20%), 66.63 (75%), and 88.31 (90%).  The use of digital learning media with the picture story "Misi Mencari Arti Nama" can have an impact on the learning outcomes of class II students at SDN Krembangan Selatan VII18 related to punctuation material in Indonesian lessons, according to research findings